Thermophysical Coefficients of Mustard Seeds Grain-Air Mixture under High-Temperature Conditions - A. P. Evdokimov; A. A. Leshchenko (Сельскохозяйственные машины и технологии, 2024)
The paper highlights that modeling the drying process of mustard seed samples using thermogravimetric moisture measurement enables the identification of the most effective design options for drying chambers. In this process, mustard seeds form a grain-air mixture with specific thermophysical properties. (Research purpose) To measure the key thermophysical coefficients of the mustard grain-air mixture at different moisture content levels and high temperatures. (Materials and methods) Mustard seed samples with moisture content ranging from 3.24 to 15.07 percent were used. The cylindrical layer method enables uniform heat distribution by positioning the heater at the center of the material layer. Experimental setups were designed to measure the thermal conductivity and thermal diffusivity coefficients of the mustard seeds, while the volumetric and specific heat capacity coefficients were calculated. (Results and discussion) Graphs illustrating the dependence of thermal conductivity, thermal diffusivity, volumetric and specific heat capacity, as well as the bulk density of the mustard seed grain-air mixture on moisture content were constructed. Approximating functions for these dependencies were identified within the studied range. (Conclusions') In the moisture content ranged from 3.24 to 15.07 percent, the thermal conductivity coefficient of the mustard seed grain-air mixture increases from 0.156 to 0.176 kW/(m·K); the thermal diffusivity coefficient rises from 6.29·10-8 to 7.70·10-8 m2/s; while the volumetric heat capacity of the mixture decreases from 2490.8 to 2286.9 kJ/(m3·K). It was found that the bulk density initially increases within the same moisture content range, reaching a maximum at around 7.5 percent, and then decreases. Conversely, the specific heat capacity decreases to a minimum point at approximately 9 percent moisture content, and then begins to rise.